2015
DOI: 10.1186/s12916-015-0415-3
|View full text |Cite
|
Sign up to set email alerts
|

What do people really think of generic medicines? A systematic review and critical appraisal of literature on stakeholder perceptions of generic drugs

Abstract: BackgroundConsiderable emphasis is presently being placed on usage of generic medicines by governments focussed on the potential economic benefits associated with their use. Concurrently, there is increasing discussion in the lay media of perceived doubts regarding the quality and equivalence of generic medicines. The objective of this paper is to report the outcomes of a systematic search for peer-reviewed, published studies that focus on physician, pharmacist and patient/consumer perspectives of generic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
1
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 80 publications
7
128
1
20
Order By: Relevance
“…A systematic review and critical appraisal had suggested information and education regarding bioequivalence, regulations and quality of generic medicines can improve prescription of these drugs. 19 Respondents expressed variable opinions regarding regulation of compulsory prescription of generic drugs in a tertiary care teaching hospital. While compulsory prescription can greatly reduce healthcare expenditure, prescribers may have apprehensions regarding quality and efficacy of these drugs and hence, some (18%) chose not to agree.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and critical appraisal had suggested information and education regarding bioequivalence, regulations and quality of generic medicines can improve prescription of these drugs. 19 Respondents expressed variable opinions regarding regulation of compulsory prescription of generic drugs in a tertiary care teaching hospital. While compulsory prescription can greatly reduce healthcare expenditure, prescribers may have apprehensions regarding quality and efficacy of these drugs and hence, some (18%) chose not to agree.…”
Section: Discussionmentioning
confidence: 99%
“…Focus groups conducted at the American College of Physicians (ACP) Internal Medicine Meeting showed that providers have low knowledge of FDA bioequivalence standards and concerns of decreased efficacy of generic options, commenting that “generics are not going to be efficacious.” Participants identified potential solutions to generic prescribing, including increased access to information and educational material about generic medication. Additionally, Dunne et al showed “a key factor in improving the confidence of…(physicians) is the provision of information and education, particularly in the areas of equivalency, regulation and in dispelling myths about generic medicines.”…”
Section: Methodsmentioning
confidence: 99%
“…A US survey of specialty physicians prescribing biologics conducted between November 2015 and January 2016 found a general lack of understanding and pressing need for education about biosimilars, particularly about the FDA approval process; the definition, safety, and efficacy of biologics versus biosimilars; and regulatory guidance for indication extrapolation, interchangeability, and pharmacy-level substitution 45. The generic market serves as an example of how practice changes as clinicians become more familiar with these alternate products (in particular, the uptake of generics such as warfarin and thyroid medication) 55–57. Biosimilar uptake ultimately depends upon education – increased understanding about biosimilar production, regulation, and mechanism of action as well as experience in clinical practice.…”
Section: Introduction To Health Care Reform In the Usamentioning
confidence: 99%